Severe localised granulomatosis with polyangiitis (Wegener’s granulomatosis) manifesting with extensive cranial nerve palsies and cranial diabetes insipidus: a case report and literature review - Peters, James E. (BMC Neurol, 2018)
BACKGROUND: Granulomatosis with polyangiitis (GPA, formerly Wegener’s granulomatosis) is a multisystem vasculitis of small- to medium-sized blood vessels. Cranial involvement can result in cranial nerve palsies and, rarely, pituitary infiltration. CASE PRESENTATION: We describe the case of a 32 year-old woman with limited but severe GPA manifesting as progressive cranial nerve palsies and pituitary dysfunction. Our patient initially presented with localised ENT involvement, but despite treatment with methotrexate, she deteriorated. Granulomatous inflammatory tissue around the skull base resulted in cavernous sinus syndrome, facial nerve palsy, palsies of cranial nerves IX-XII (Collet-Sicard syndrome), and the rare complication of cranial diabetes insipidus due to pituitary infiltration. The glossopharyngeal, vagus and accessory nerve palsies resulted in severe dysphagia and she required nasogastric tube feeding. Her neurological deficits substantially improved with treatment including high dose corticosteroid, cyclophosphamide and rituximab. CONCLUSIONS: This case emphasises that serious morbidity can arise from localised cranial Wegener’s granulomatosis in the absence of systemic disease. In such cases intensive induction immunosuppression is required. Analysis of previously reported cases of pituitary involvement in GPA reveals that this rare complication predominantly affects female patients.